Between civil wars : the caliphate of Muà̄wiyah - Ṭabarī, 838?-923 (Ṭabarī, 838?-923. Tārīkh al-rusul wa-al-mulūk., 1987)
This volume presents for the first time in English Tabari's complete account of the twenty-year long reign of the fifth caliph, Mu'awiyah (661-680). The importance of this account lies partly in Tabari's quotation of major portions of the work of earlier authors, such as Abu Mikhnaf and other eighth-century compilers. It is also significant because Tabari's selection of themes has had a decisive influence on modern interpretations of this period, particularly on the identification of what the important issues were in the works of Henri Lammens and Julius Wellhausen. Here one can read the exciting account of the Khariji revolt of Mustawrid ibn Ullifah, the impressive but controversial record of the governorship of Ziyad b. Abihi, the entertaining escapades of the poet Farazdaq in his youth, and the tragic story of Hibn 'Adi. Tabari's presentation of different points of view about these and other events makes his account an indispensable source for early Islamic history.